Heterogeneity of the purified extracellular aspartyl proteinase from Candida albicans: characterization with monoclonal antibodies and N-terminal amino acid sequence analysis. - Morrison, C J (1993)
Three dominant proteins (41, 48, and 49 kDa) were detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) in purified preparations of the extracellular aspartyl proteinase (AP) of Candida albicans. All three proteins bound to the specific carboxyl proteinase ligand, pepstatin A, and were associated with maximum AP activity. The N-terminal amino acid sequence for the 48- and 49-kDa proteins matched that reported by others for AP, whereas the sequence for the 41-kDa protein was unique and was not homologous to any known protein. Time course studies demonstrated the simultaneous presence of all three proteins, supporting evidence that the 41- and 48-kDa proteins were not breakdown products of AP. Previous studies did not detect carbohydrate in SDS-polyacrylamide gels of purified AP preparations stained with periodic acid and silver, making glycosylation an unlikely explanation for the observed differences in the molecular masses of the proteins. Some monoclonal antibodies directed against the 49-kDa protein reacted with the 41- and 48-kDa proteins, indicating cross-reactive epitopes. Other monoclonal antibodies, however, reacted only with the 49-kDa protein. We conclude that three pepstatin A-binding proteins occur in purified AP preparations: two have the same amino acid N terminus as that reported for AP, whereas the third has a unique sequence. All three proteins should be considered when undertaking studies to determine the role of AP in candidal pathogenesis or when preparing specific antibodies for antigen capture assays.